2020
DOI: 10.3390/polym13010085
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Reduced Graphene Oxide/Thermoplastic Polyurethane Nanocomposites: Mechanical and Barrier Properties

Abstract: This work consists of studying the influence of two thermally reduced graphene oxides (TRGOs), containing oxygen levels of 15.8% and 8.9%, as fillers on the barrier properties of thermoplastic polyurethane (TPU) nanocomposites prepared by melt-mixing processes. The oxygen contents of the TRGOs were obtained by carrying out the thermal reduction of graphene oxide (GO) at 600 °C and 1000 °C, respectively. The presence and contents of oxygen in the TRGO samples were determined by XPS and their structural differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…With the increase of GDs content, the mechanical properties of composite materials show a trend of increasing at first and then decreasing (Du et al, 2020). In addition, different interface binding modes (Compton et al, 2012;Park et al, 2008), oxygen content in GO (Maldonado-Magnere et al, 2020), and different manufacturing processes (Gallardo-Lopez et al, 2020) can affect the mechanical properties of graphene composites, which makes the mechanical properties of graphene composites tunable. Therefore, it is theoretically possible for GMs to mimic the properties of bone, which is extremely exciting in bone tissue engineering.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…With the increase of GDs content, the mechanical properties of composite materials show a trend of increasing at first and then decreasing (Du et al, 2020). In addition, different interface binding modes (Compton et al, 2012;Park et al, 2008), oxygen content in GO (Maldonado-Magnere et al, 2020), and different manufacturing processes (Gallardo-Lopez et al, 2020) can affect the mechanical properties of graphene composites, which makes the mechanical properties of graphene composites tunable. Therefore, it is theoretically possible for GMs to mimic the properties of bone, which is extremely exciting in bone tissue engineering.…”
Section: Mechanical Propertymentioning
confidence: 99%
“…Various studies have found that the mechanical properties of graphene and its derivatives are affected by different interface binding modes, oxygen content, and different manufacturing processes, which makes the mechanical properties of graphene and its derivatives adjustable [ [40] , [41] , [42] ]. Therefore, graphene and its derivatives can theoretically mimic the mechanical properties of human bone and have broad prospects in the field of bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the elongation at break of treated PLA/NFH biocomposite films with 3-APE decreased around 6 % in comparison with untreated PLA/NFH biocomposite films. The decreasing of the elongation at break of treated PLA/NFH biocomposite films was due the 3-APE treatment has improved the tensile strength of biocomposite films with the enhancement in rigidity and decrement of the ductility of biocomposite films [25].…”
Section: Tensile Propertiesmentioning
confidence: 98%